Hubungan Antara Usia Ibu Hamil dengan Preeklampsia Tipe Lambat di Rumah Sakit PKU Muhammadiyah Surabaya - Mustofa, Ali; Ariningtyas, Ninuk Dwi; Prahasanti, Kartika; Anas, Muhammad (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2021)
Preeclampsia is one of the most common complications in pregnancy that can lead to various complications such assevere illness, long-term disability, andmaternal, fetal, and neonatal mortality. The prevalence of preeclampsia, 30%-40% can cause maternal mortality, and 30%-50% can lead to perinatal mortality. Maternal age is one of the riskfactors for late-onset preeclampsia. Maternal age is grouped into two categories; extreme age (<20 years and> 35 years)and reproductive age (21-35 years). This studyaims to determine the relationship between maternal age and late-onsetpreeclampsia at PKU Muhammadiyah Surabaya Hospital from January to June 2020. The research method used isobservational analytic with case control design. The samples involved were pregnant women visiting PKUMuhammadiyah Surabaya Hospital from January to June 2020. The data were analyzed using a statistical test ofcontingency coefficient correlation. The results showed that respondents who experienced late-onset preeclampsia inthe extreme age group (<20 years and> 35 years) were 37 respondents (100%) and in reproductive age (21-35 years)were 28 respondents (80%), the respondent who did not experience late-onset preeclampsia in extreme ages (<20 yearsand> 35 years) was 0 respondents(0%) and in reproductive age (21-35 years) were 7 respondents (20%). The resultsof the statistical test for the contingency coefficient correlation showed a p-value of 0.004 below (â‰¤0.05). All thingsconsidered, there was a significant relationship between maternal age and late-onset preeclampsia at the PKUMuhammadiyah Surabaya Hospital from January to June 2020.